Radiological anatomy of the vertebrobasilar artery in a select South African population - Ezra E. Anirudh; Bukola R. Omotoso; Lelika Lazarus, PhD (Elsevier, 2022)
Introduction: The vertebrobasilar artery is the combination of the bilateral vertebral artery and the basilar artery. The basilar artery extends from the confluence of the bilateral vertebral arteries at the pontomedullary junction, terminating at the ponto-mesencephalic junction. Depending on the geometry of the intracranial vertebral arteries and the incidence of arterial tortuosity, the basilar artery may exhibit variable course patterns. This morphologic deformation has negative implications on the hemodynamic of blood flow in the posterior circulatory territory by inducing the development of infarcts and thus increasing the risk of vascular pathologies. Lateral displacement of the basilar artery has been associated with migraines and frequent headaches. The present study aimed to investigate the radiological anatomy of the basilar artery within a select South African cohort of patients in terms of the course patterns and morphometry. Materials and method: The study is an observational retrospective chart review of 100 radiographic images (Average age: 59; Males: 60%; Females: 40%) of multidetector computed tomography angiography, of the vertebrobasilar artery to establish the course pattern of the basilar artery. Results: Asymmetry of the intracranial vertebral artery as well as lateral displacement of the basilar artery have been reported with varying course patterns. The average length and diameter of the basilar artery were reported as 25.41 ± 6.44 mm 2.72 ± 0.85 mm, respectively. Conclusion: The geometric characteristics of the vertebrobasilar system in the population studied can predispose to some cerebrovascular diseases in the posterior circulatory territory and influence the build-up of atherosclerotic plaque. Knowledge of this variant anatomy is imperative to the clinician in the diagnosis of many vascular-related pathologies.